Relationship between periodontal diseases and newly-diagnosed metabolic syndrome components in a sub-Saharan population: a cross sectional study - Jean Xavier Ekouelkoum Ngoude; Vicky Jocelyne Ama Moor; Tsobgny Tsague Nadia-Flore; Batakeh B. Agoons; Gamgne Guiadem Catherine Marcelle; Elage Epie MacBrain; Daryl Nzokou Tcheutchoua; Jan René Nkeck (BMC, 2021)
Abstract Background Oral health is a frequently ignored aspect of global health in sub-Saharan patients. Periodontitis, a very frequent oral disease has been proven to be associated to development of the metabolic syndrome. This study aims to evaluate the relationship between periodontal disease and metabolic syndrome components in a sub-Saharan population. Methods We performed a cross sectional study in 3 Yaounde hospitals. Consenting adults aged 21 years and above were recruited. Participants who presented with a tooth loss of at least 50% or any condition which could alter values of biological and periodontal parameters (tobacco smoking, pregnancy, chronic kidney disease, cancer) were excluded. Metabolic syndrome elements (glycaemia, arterial pressure, HDL cholesterol, abdominal circumference, triglycerides) and periodontal variables were recorded (plaque and gingival index of Silness and Loe, periodontal pocket depth and clinical attachment loss). These variables were compared using Fisher's exact Test and odds ratio calculated with 95% confidence intervals. Results The prevalence of periodontitis and metabolic syndrome were 43.4% and 10.8% respectively. Age (37.75 ± 13.25, P < 0.001) and poor accessory brushing methods were associated risk factors for development of periodontal disease. Sub-Saharan sindividuals with periodontitis had increased odds of having obesity (OR 11.1 [95% CI 3.97-31.03], P < 0.001) and low HDL (OR 4.58 [95% CI 1.79-11.70], P = 0.001) Conclusion Our findings suggest an association between periodontal disease and metabolic syndrome in Sub-Saharan subjects. Increasing age and poor accessory brushing methods are associated risk indicators.